Factors that influence the Competence and Productivity of Islamic Boarding School Educators and Employees - Afiqah Hasbullah; Irma Herliza Rizki; Putri Mauliza (Outline Publisher, 2024)
This community service activity aims to improve the competence and productivity of teachers and employees of Islamic boarding schools through mentoring in Human Resources (HR) management. In this activity, an initial assessment was carried out to identify development needs, followed by training in technical skills, time management, and the use of technology in learning. Mentoring also includes coaching and mentoring sessions to strengthen managerial skills and increase motivation and job satisfaction. The results of this activity showed a significant increase in teaching competence, classroom management, and use of technology. In addition, the work productivity of participants also increased, reflected in increased time efficiency and quality of work. Participants' job satisfaction increased, which contributed to the creation of a more positive work environment. Overall, this mentoring succeeded in providing a positive impact on teachers and employees of Islamic boarding schools in improving the quality of work and management of Islamic boarding schools, as well as supporting the achievement of goals.